Legal problems in the parallel sale of products luxury (“accessible”): A multi-billion dollar industry that plays both sides? - Antón Juárez, Isabel (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
Parallel trade is neither a new nor recent phenomenon. However, it is currently still a cause of concern for luxury brands. This industry, which had a turnover of more than 1.5 trillion dollars in 2024, aims at the most mundane desires of mortals without leaving their deepest dreams indifferent. The purpose of this work is threefold. On the one hand, the luxury industry today will be analyzed, including figures, protagonists and way of operating. All this to reach a second part and highlight the way in which they build that dream that everyone wants (or we want) and that from our point of view, distribution plays a key role. However, every dream, even if it is well built, can slip through our fingers, fragility is inherent to human beings and luxury brands are not immune. Proof of that fragility, and that no matter how well you have everything designed from a business perspective, there may be leaks, is parallel trade. Luxury brands are companies where every detail has been analyzed, however, despite this, parallel trade continues to exist. In this work we are going to analyze the reason for its existence and the legal problems it raises from a perspective mainly of European trademark law.
Keywords: parallel distribution; luxury products; authorized distributor; cross border trade